2007
DOI: 10.1111/j.1744-313x.2007.00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to Newcastle disease virus in chicken lines divergently selected for cutaneous hypersensitivity

Abstract: This paper describes for the first time the differential immune response to virulent Newcastle disease virus (NDV) in birds differing in cell-mediated immunity, as measured by response to phytohaemagglutinin-P. To explore potential host-pathogen interactions, peripheral blood mononuclear cells (PBMC) were collected from 40 extreme responder birds (20 birds each from high and low cell-mediated immunity lines). PBMC cultures were stimulated by virulent NDV and temporal expression profiles of interferon-gamma (IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 68 publications
(94 reference statements)
2
25
0
1
Order By: Relevance
“…We observed a higher level of NO in intestinal mucosa in NDV challenged groups compared to control. Our results are in agreement with the Ahmed, et al [33]. and Lam, et al [34].…”
Section: Discussionsupporting
confidence: 83%
“…We observed a higher level of NO in intestinal mucosa in NDV challenged groups compared to control. Our results are in agreement with the Ahmed, et al [33]. and Lam, et al [34].…”
Section: Discussionsupporting
confidence: 83%
“…Research has shown that, in chicken cells, NDV can induce nitric oxide (NO) in vitro in heterophils (Sick et al, 2000) and peripheral blood mononuclear cells (Ahmed et al, 2007), alpha (IFN-a) and beta (IFN-b) interferon mRNA in macrophages (Sick et al, 1998) and gamma interferon (IFN-c) mRNA in peripheral blood mononuclear cells (Ahmed et al, 2007). Yet this existing knowledge of the in vitro response to NDV is insufficient to understand the nature of the host response to virulent NDV in vivo or to understand the underlying mechanisms of pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The ND virus infection in-vitro induced by Nitric Oxide on heterophile chicken. 11 PBMC also showed that IFNγ that IFNß in mRNA can be detected in macrophages. The discovery of drugs derived from plants which modulate the function of CD4 + and CD8 + are important for the potential therapeutic of compounds.…”
Section: Methodsmentioning
confidence: 93%
“…The data analysis results for the secretion of IFNγ showed that the control group + (K + ), P0, P1 and P2 has a value secretion higher than the group control-(K), because ND virus inoculation can increase the secretion of IFNγ. 11,15 Among the highest valued treatment group for the secretion of IFNγ, the treatment group 2 (P2) shows that the administration of 10μg dose Tenggulun leaf extract is the most effective to increase the secretion of IFNγ. The increased secretion of IFNγ may be caused by Tenggulun leaves' terpenoids as the antibacterial and anti-inflammatory compounds.…”
Section: Methodsmentioning
confidence: 99%